Conversational Implicature in the Food Product Advertisement: There is Taste, There is Price - Sari, Putri Ardina Setia; Rosita, Farida Yufarlina; Pancarrani, Berlian (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This study explores the use of conversational implicature in the "Sasa Tepung Bumbu Premium Collection" advertisement, with a specific focus on the slogan "Ada Rasa Ada Harga" (There is Taste, There is Price). It aims to uncover how the advertisement conveys persuasive and symbolic messages through deliberate violations of Grice's maxims. Combining pragmatic discourse analysis with a multimodal framework, the study analyzes verbal utterances alongside visual elements such as gesture, tone, music, and scene composition. Findings reveal that the advertisement uses ambiguity, metaphor, and visual reinforcement to construct emotional and symbolic value. The novelty lies in its integration of implicature theory, affective marketing, and multimodal analysis in the Indonesian advertising context, offering both academic insights and practical implications for marketers.